2005
DOI: 10.1590/s0004-282x2005000600006
|View full text |Cite
|
Sign up to set email alerts
|

Headaches during pregnancy in women with a prior history of menstrual headaches

Abstract: -Objective: To evaluate the presence of menstrual headaches prior to pregnancy according to the International Headache Society (IHS) classification criteria, 2004, and also study the outcome (fre q u e ncy and intensity) of these pre-existing headaches during the gestational trimesters. Method: This study involved 1,101 pregnant women (12 to 45 years old). A semi-stru c t u red questionnaire was used to interview the women during the first, second and third gestational trimesters as well as after delivery. All… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
3

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 20 publications
1
17
0
3
Order By: Relevance
“…1). Improvement is more likely in women with a history of MM [7, 30, 31]. If migraine does not improve by the end of the first trimester, it is likely to continue throughout the pregnancy [32].…”
Section: Migraine During Women’s Lifementioning
confidence: 99%
“…1). Improvement is more likely in women with a history of MM [7, 30, 31]. If migraine does not improve by the end of the first trimester, it is likely to continue throughout the pregnancy [32].…”
Section: Migraine During Women’s Lifementioning
confidence: 99%
“…Several studies have shown that about one-half to three-fourths of female migraineurs experience a reduction in the frequency or total cessation of migraine attacks during pregnancy [112], mainly in the second and third trimesters [5, 7, 11, 13, 14]. In addition, the average pain intensity of the remaining attacks decreases as the pregnancy proceeds [10].…”
Section: Introductionmentioning
confidence: 99%
“…If migraine is not improved by the end of the first trimester, it is likely to continue throughout the pregnancy and postpartum periods [15]. The improvement seems to be especially prominent in women with perimenstrual or pure menstrual migraine [1, 3, 4, 7, 9], and one study has shown that women having migraine without aura are more likely to become better than women having migraine with aura [2]. …”
Section: Introductionmentioning
confidence: 99%
“…Respite is greater for women with a history of menstrual or menstrually related migraine without aura than for women with no evidence of a menstrual association. [8][9][10] Migraine with aura In contrast to migraine without aura, women who have preexisting migraine with aura are more likely to continue to have attacks during pregnancy. 9 Women with pre-existing migraine without aura may develop aura for the first time during pregnancy.…”
Section: Migraine Without Auramentioning
confidence: 99%
“…Olesen (1992) 66 Granella et al 67 Chen and Leviton (1994) 68 Cupini et al 69 Scharff et al 26 Maggioni et al 16 Marcus et al 7 Granella et al 9 Sances et al 8 Kelman (2004) 70 Melhado et al 10 Ertresvag et al Of all the parameters studied, the only positive finding was that limb deficiencies were associated with a higher rate of maternal migraines during the first trimester of pregnancy, for both the congenital abnormalities group vs matched normal group (adjusted POR 2.5, 95% CI 1.1-5.8) and the congenital abnormalities group vs Down syndrome controls (adjusted POR 1.7, 95% CI 1.3-3.0). Although this study has the benefit of large numbers, these data are not confirmatory and the effect of other independent variables, drug and non-drug treatments taken, and misdiagnosis of conditions mimicking migraine cannot be ruled out.…”
Section: Studymentioning
confidence: 99%